Production of amylases by yeasts - Linardi, V. R.; Machado, K. M.
Yeasts (228)isolated for natural habitats were screened for their ability to produce amylases in semisolid medium of wheat bran. Strains of Aureobasidium pullulans, Candida famata, and Candida kefyr showed high enzymatic activity for a-amylase, glucoamylase, and debranching enzyme. Key words: Aureobasidium, Candida, amylolytic yeasts, a-amylase, glucoamylase.
Keywords: AUREOBASIDIUM, CANDIDA; AMYLOLYTIC YEASTS; A-AMYLASE, GLUCOAMYLASE